Saint Raphael of Banat in the Context of Historical and Ethnological Sources - Воргић, Дејан (Sabornost - The Theological Year-book, 2016)
This research primarily aims to shed light on the historical circumstances of life and death St. Raphael of Banat. In a special segment of this work, the emphasis will be on the existence of a monastery with a dedication Presentation of the Virgin at the end of the seventeenth century in Becskerek where short‑term stayed and died monk Rafailo. At the beginning of XVIII century there is the development of the cult dedicated to this a monk, and this research will investigate all segments of its manifestation, to church Parliament’s official canonization in 1965.